Method for measuring contents of ferrous iron, ferric iron and elemental iron in copper sponge
By using pure water and citric acid immersion methods in sponge copper, selectively immerse the two -price iron and three -valent iron, and use the inductive coupling plasma to transmit the spectral concentration of iron ions to solve the measurement of the iron content of the sponge copper in the existing technology The accuracy and repetitive problems have achieved efficient and accurate iron group analysis.
Patent Information
- Application Number
- CN202411589342.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to accurately determine the content of divalent, trivalent and elemental iron in sponge copper, and there is interference with copper on the iron detection results, and the measurement process is complicated and the accuracy and repeatability are poor.
Pure water and citric acid are immersed in sequentially, selectively immersed the two -price iron and triple iron, respectively, and the iron ion concentration was determined by the inductive ion reactoring the spectral method to eliminate the interference of copper.
The accurate determination of the two -valent iron, three -valent iron, and single -quality iron content of sponge copper, avoiding the interference of copper, simplified the analysis process, and improved the accuracy and repetitiveness of the determination results.
Smart Images

Figure CN119354949A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of zinc smelting detection, and in particular to a method for determining the contents of divalent iron, trivalent iron and elemental iron in sponge copper. Background Art
[0002] Sponge copper, its copper powder is reddish brown powder. High-grade sponge copper powder is a very important industrial raw material, which can be used to refine metallic copper and make raw materials such as cuprous octoate, and is widely used in the manufacture of various copper alloys, precision castings and other parts to replace copper materials.
[0003] The sponge copper produced by the purification process in the zinc hydrometallurgy process is an important embodiment of the comprehensive utilization of resources. On the one hand, it reduces the negative impact of smelting slag on the environment; on the other hand, it provides raw materials for copper smelting and saves the consumption of copper ore resources. Copper slag is leached with dilute sulfuric acid or waste electrolyte, and replaced with iron powder to obtain sponge copper. However, in the actual replacement process, in order to completely replace copper, excessive iron powder must be added. The iron powder is difficult to react completely, and some iron powder is entrained in the sponge copper or wrapped by the sponge copper, or the free acid in the replacement liquid is too low. When the acidity rises to pH=3, the ferric sulfate will begin to hydrolyze, thereby precipitating insoluble iron hydroxide precipitation, which flows into the sedimentation tank together with the product sponge copper. Therefore, the sponge copper obtained from the sedimentation tank contains iron impurities. Determining the elemental iron content in sponge copper can be used as a reference standard for the amount of reduced iron powder added. Therefore, in-depth analysis of the iron component is of great significance for revealing the distribution characteristics of each component in sponge copper, exploring the element occurrence state and removing iron impurities in sponge copper. Given the particularity of mutual interference between copper and iron in sponge copper during analysis and detection, the quantitative analysis of the accurate determination of the iron component faces great challenges.
[0004] The copper in sponge copper mainly exists in the form of single copper, and iron exists in the form of single iron, divalent iron, and trivalent iron. At present, the determination method of divalent iron and trivalent iron content mainly adopts wet chemical analysis and testing, grinding the sample, then dissolving it into a solution, and then measuring the result by titration or colorimetry. The whole analysis process is complicated, labor-intensive, and time-consuming. Among them, there are also strict requirements on the dissolution treatment conditions, and Fe in the solution should be avoided as much as possible. 2+ Oxidized to Fe 3+ Otherwise, a large error will occur. In actual operation, to prevent Fe 2+ Oxidized to Fe 3+ The operation method is difficult to master, and the accuracy and repeatability of the measured data are poor. In addition, when sponge copper is dissolved in acid, copper and elemental iron will also be dissolved. When the potassium dichromate method is used to determine the iron content, Cu 2+ Easily reduced to Cu by trivalent titanium ions + , and Cu +It will be oxidized by potassium dichromate, which will result in a high iron content test result. In addition, the oxidized copper ions will oxidize ferrous ions, which will result in a low iron content test result. At the same time, the separation procedure is complicated, and it is impossible to achieve accurate quantitative analysis of the various iron components in sponge copper.
[0005] The main methods for determining the content of elemental iron are HgCl2 method, copper salt method and FeCl3 method. The HgCl2 method is the oldest analytical method. Since the Hg and Hg2Cl2 colloidal precipitation generated by reduction wrap the metallic iron particles, the elemental iron cannot be quantitatively oxidized, resulting in a low measurement result. In addition, the analysis process is cumbersome, HgCl2 is a highly toxic reagent, and it is difficult to recycle and treat, which does not meet the analytical standards for environmental protection. The FeCl3 method is currently the conventional method for analyzing elemental iron. Ferric chloride can oxidize elemental copper while oxidizing elemental iron, which affects the determination of elemental iron content and has low accuracy.
[0006] In view of this, it is urgent to establish a method that can accurately determine the content of divalent iron, trivalent iron and elemental iron in sponge copper. Summary of the invention
[0007] In order to solve or partially solve the problems existing in the related art, the present application provides a method for determining the content of divalent iron, trivalent iron and elemental iron in sponge copper. The determination method can accurately determine the content of divalent iron, trivalent iron and elemental iron in sponge copper, and avoid the interference of copper in sponge copper.
[0008] The present application provides a method for determining the content of divalent iron, trivalent iron and elemental iron in sponge copper, comprising the following steps:
[0009] 1) leaching the sponge copper with water to obtain a leaching solution and a leaching residue;
[0010] 2) leaching the leached residue with citric acid to obtain citric acid leaching solution and citric acid leached residue;
[0011] The concentrations of iron ions in the leaching solution, citric acid leaching solution and citric acid leaching residue were determined respectively, and the content of divalent iron, trivalent iron and elemental iron in the sponge copper were obtained respectively.
[0012] Optionally, the mass concentration of citric acid in step 2) is 10%-20%.
[0013] Optionally, in step 2), the pH of the citric acid is 3.5-4.0.
[0014] Optionally, in step 2), the ratio of leached residue to citric acid (g:ml) is (0.6-1.2):50. The mass of the leached residue is water-containing leached residue.
[0015] Optionally, in step 2), the leaching time is 40-60 min and the leaching temperature is 50-100°C.
[0016] Optionally, in step 1), the dosage ratio (g:ml) of sponge copper to water is (0.5-1):50; and the leaching time is 20-30 min.
[0017] Optionally, in step 1), the leaching time is 20-30 min; and the leaching temperature is 50-100°C.
[0018] Optionally, hydrochloric acid is used to dissolve the citric acid leaching residue, the mass concentration of the hydrochloric acid is 36%-38% and the dissolution temperature is 100-200°C.
[0019] Optionally, the ratio of citric acid leaching residue to hydrochloric acid (g:ml) is (0.3-0.6):30.
[0020] The present application uses pure water and citric acid to selectively leach divalent iron and ferric iron in turn, so as to separate divalent iron, ferric iron from elemental copper and elemental iron. In the final hydrochloric acid dissolution process, although elemental iron and elemental copper have been dissolved, copper may interfere with the determination of iron if potassium dichromate titration is used. However, the present application uses inductively coupled plasma emission spectrometry to eliminate the interference of copper on iron.
[0021] Citric acid solution can dissolve both divalent and trivalent iron, but in actual operation, it is necessary to prevent Fe 2+ Oxidized to Fe 3+ The operation method is difficult to master, and the accuracy and repeatability of the measured data are poor. Therefore, in this application, the sponge copper is heated and leached with water to remove the divalent iron to avoid the interference of the divalent iron in the determination of trivalent iron. Citric acid has a strong chelating effect and can dissolve metal oxides such as ferric hydroxide. Since it does not contain Cl- in the molecule, it has very low solubility in elemental iron. It can complex Fe 3 +, it has almost no dissolution of elemental iron under low concentration and near-neutral conditions. However, other acids are too acidic, so it is difficult to adjust the pH to just dissolve ferric hydroxide without reacting with elemental iron in actual operation.
[0022] The chemical reaction equation for citric acid leaching is as follows:
[0023] C6H8O7+Fe(OH)3→C6H5FeO7+3H2O
[0024] The chemical reaction equation for dissolution is as follows:
[0025] 2Cu+4HCl=2H[CuCl2]+H2↑
[0026] Fe+2HCl=FeCl2+H2↑
[0027] The calculation formula in the present invention is preferably:
[0028]
[0029] X is Fe 2+ , Fe 3+ 、Fe(element);
[0030] C1 is the iron ion concentration;
[0031] V1 is the volume of the filtrate and the dissolved solution.
[0032] The technical solution provided by this application may have the following beneficial effects:
[0033] 1) In the application, the sponge copper is heated with water to leach the divalent iron, and the divalent iron is accurately determined while avoiding the interference of the divalent iron with the determination of the trivalent iron.
[0034] 2) The present application controls the concentration and pH of citric acid to make citric acid complex the trivalent iron in the sponge copper, thereby separating the trivalent iron from the elemental iron.
[0035] 3) The present application adopts pure water and citric acid to selectively leach divalent iron and trivalent iron in turn, which can achieve accurate determination of divalent iron, trivalent iron and elemental iron in sponge copper.
[0036] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and other objects, features and advantages of the present application will become more apparent through a more detailed description of exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.
[0038] Figure 1 It is a schematic diagram of the determination process of the content of divalent iron, trivalent iron and elemental iron in sponge copper shown in the present application. DETAILED DESCRIPTION
[0039] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.
[0040] Example 1
[0041] In this example, sponge copper 1# produced by hydrometallurgy was selected for determination, and the known components are shown in Table 1.
[0042] Table 1 Content of each component of sponge copper 1
[0043] Components Cu(element) TFe Fe(element) <![CDATA[FeSO4]]> <![CDATA[Fe(OH)3]]> Contains (wt.%) 81.80 10.99 6.44 9.79 1.82
[0044] Fe in FeSO4 in Table 1 2+ The content of Fe(OH)3 is 3.60%. 3+ The content is 0.95%.
[0045] 1) Grind the sponge copper synthetic slag to 180 mesh, weigh 0.70000g (record the mass as m) of sponge copper and place it in a 250ml beaker, add 50ml of secondary deionized water, heat to 60°C, leach for 20min, filter and wash, the solution obtained by filtration is the leachate, the residue obtained is the leachate residue, the mass of the leachate residue is 0.78g (the leachate residue is the water-containing leachate residue), transfer the filtrate into a 100ml volumetric flask and make up the volume (record the volume as V1), and determine the iron ion concentration by inductively coupled plasma emission spectrometry to be 254.8mg / L (record the concentration as C1);
[0046] 2) placing the leached residue in the original beaker, adding 50 ml of 15% citric acid solution (pH=3.7), heating to 60°C and leaching for 40 min, filtering and washing, the solution obtained by filtration is the citric acid leaching solution, and the residue obtained is the citric acid leaching residue;
[0047] 3) The citric acid leaching solution was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V2), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry to be 64.4 mg / L (the concentration was recorded as C2); the citric acid leaching residue was placed in the original beaker, 30 ml of hydrochloric acid was added, the mass concentration of concentrated hydrochloric acid was 37%, and the solution was heated to 100 ° C to dissolve, i.e., the hydrochloric acid solution was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V3), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry to be 448.7 mg / L (the concentration was recorded as C3).
[0048] The content of divalent iron in sponge copper is:
[0049] The content of trivalent iron in sponge copper is:
[0050] The elemental iron content in sponge copper is:
[0051] Example 2
[0052] In this example, sponge copper 2# produced by hydrometallurgy was selected for determination, and the known components are shown in Table 2.
[0053] Table 2 Content of each component of sponge copper 2
[0054] Components Cu(element) TFe Fe(element) <![CDATA[FeSO4]]> <![CDATA[Fe(OH)3]]> Contains (wt.%) 78.53 12.87 8.15 8.89 2.78
[0055] Fe in FeSO4 in Table 2 2+ The content of Fe(OH)3 is 3.27%. 3+ The content is 1.45%.
[0056] 1) Grind the sponge copper synthetic slag to 190 mesh, weigh 0.80000g (record the mass as m) of sponge copper and place it in a 250ml beaker, add 50ml of secondary deionized water, heat to 70°C and leach for 23min, then filter and wash, the solution obtained by filtration is the leachate, the residue obtained is the leachate residue, the mass of the leachate residue is 0.89g (the leachate residue is the water-containing leachate residue), transfer the filtrate into a 100ml volumetric flask and make up the volume (record the volume as V1), and determine the iron ion concentration by inductively coupled plasma emission spectrometry to be 256mg / L (record the concentration as C1);
[0057] 2) placing the leached residue in the original beaker, adding 50 ml of 10% citric acid solution (pH=3.8), heating to 70°C and leaching for 45 min, filtering and washing, the solution obtained by filtration is the citric acid leaching solution, and the residue obtained is the citric acid leaching residue;
[0058] 3) The filtrate was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V2), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry, which was 120 mg / L (the concentration was recorded as C2); the citric acid leaching residue was placed in the original beaker, 30 ml of concentrated hydrochloric acid was added, and the mass concentration of the concentrated hydrochloric acid was 38%, and the solution was heated to 150° C. to dissolve, and the resulting solution was the hydrochloric acid solution, which was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V3), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry, which was 654.4 mg / L (the concentration was recorded as C3).
[0059] The content of divalent iron in sponge copper is:
[0060] The content of trivalent iron in sponge copper is:
[0061] The elemental iron content in sponge copper is:
[0062] Example 3
[0063] In this example, sponge copper 3# produced by hydrometallurgy was selected for determination, and the known components are shown in Table 3.
[0064] Table 3 Content of various components of sponge copper 3
[0065] Components Cu(element) TFe Fe(element) <![CDATA[FeSO4]]> <![CDATA[Fe(OH)3]]> Contains (wt.%) 85.24 8.71 5.28 6.33 2.11
[0066] Fe in FeSO4 in Table 32+ The content of Fe(OH)3 is 2.33%. 3+ The content is 1.10%.
[0067] 1) Grind the sponge copper synthetic slag to 200 mesh, weigh 1.0000g (record the mass as m) of sponge copper and place it in a 250ml beaker, add 50ml of secondary deionized water, heat to 80°C and leach for 28min, then filter and wash, the solution obtained by filtration is the leachate, the residue obtained is the leachate residue, the mass of the leachate residue is 1.20g (the leachate residue is the water-containing leachate residue), transfer the filtrate into a 100ml volumetric flask and make up the volume (record the volume as V1), and determine the iron ion concentration by inductively coupled plasma emission spectrometry to be 228mg / L (record the concentration as C1);
[0068] 2) Place the leached residue in the original beaker, add 50 ml of 13% citric acid solution (pH = 3.9), heat to 80 ° C, leach for 55 minutes, filter and wash, the solution obtained by filtration is the citric acid leachate, and the residue obtained is the citric acid leach residue.
[0069] 3) The filtrate was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V2), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry, which was 119 mg / L (the concentration was recorded as C2); the citric acid leaching residue was placed in the original beaker, 30 ml of concentrated hydrochloric acid was added, and the mass concentration of the concentrated hydrochloric acid was 36%, and the solution was heated to 180° C. to dissolve, and the resulting solution was the hydrochloric acid solution, which was transferred into a 100 ml volumetric flask and fixed to volume (the volume was recorded as V3), and the iron ion concentration was determined by inductively coupled plasma emission spectrometry, which was 534 mg / L (the concentration was recorded as C3).
[0070] The content of divalent iron in sponge copper is:
[0071] The content of trivalent iron in sponge copper is:
[0072] The elemental iron content in sponge copper is: =5.34wt.%.
[0073] Comparative Example 1
[0074] The difference between Comparative Example 1 and Example 1 is that in step 2) of Comparative Example 1, citric acid is replaced by hydrochloric acid or sulfuric acid, and other conditions remain unchanged. The experimental results are shown in Table 4.
[0075] Table 4 Comparative Example 1 Component Contents of Sponge Copper (wt.%)
[0076] Leaching agent Fe(element) <![CDATA[Fe 2+ ]]> <![CDATA[Fe 3+ ]]> hydrochloric acid 4.20 3.60 3.18 sulfuric acid 4.65 3.62 2.68
[0077] As can be seen from Table 4, the content of elemental iron, divalent iron and ferric iron in sponge copper was determined by hydrochloric acid and sulfuric acid, and the measurement results were quite different from the true values. Therefore, citric acid was used in the present application to accurately determine the content of elemental iron, divalent iron and ferric iron in sponge copper.
[0078] Comparative Example 2
[0079] The difference between Comparative Example 2 and Example 1 is that in step 2) of Comparative Example 2, the pH of citric acid is set to 1.0 and 5.0, and other conditions remain unchanged. The experimental results are shown in Table 5.
[0080] Table 5 Comparative Example 2 Component Contents of Sponge Copper (wt.%)
[0081] pH Fe(element) <![CDATA[Fe 2+ ]]> <![CDATA[Fe 3+ ]]> 1.0 5.06 3.61 2.27 5.0 6.92 3.63 0.45
[0082] As shown in Table 5, when the pH of the citric acid in Example 1 is changed to 1.0 and 5.0, the content of elemental iron in Comparative Example 1 is 5.06wt.% and 6.92wt.%, which is far from the 6.44wt.% of elemental iron in sponge copper in Example 1; 3+ The content of Fe in sponge copper in Example 1 is 2.27wt.% and 0.45wt.%. 3+ The content is 0.95wt.%, which is far from the original value. Therefore, the use of citric acid with other pH values cannot accurately determine the elemental iron and Fe in sponge copper. 3+ .
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 1 is that in step 2) of Comparative Example 2, the concentration of citric acid is 30% and 50%, and other conditions remain unchanged. The experimental results are shown in Table 6.
[0085] Table 6 Comparative Example 3 Component Contents of Sponge Copper (wt.%)
[0086] concentration Fe(element) <![CDATA[Fe 2+ ]]> <![CDATA[Fe 3+ <!-- 5 -->]]> 30% 5.30 3.65 1.98 50% 4.32 3.62 3.04
[0087] As shown in Table 6, when the concentration of citric acid in Example 1 is changed to 30% and 50%, the content of elemental iron in Comparative Example 2 is 5.30wt.% and 4.32wt.%, which is far from the 6.44wt.% of elemental iron in sponge copper in Example 1; 3+ The content of Fe in sponge copper in Example 1 is 1.98wt.% and 3.04wt.%. 3+ The content is 0.95wt.%, which is far from the original concentration. Therefore, other concentrations of citric acid cannot accurately determine the elemental iron and Fe in sponge copper. 3+ .
[0088] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A method for determining the content of divalent iron, trivalent iron and elemental iron in sponge copper, characterized in that: The following steps are involved: 1) leaching the sponge copper with water to obtain a leaching solution and a leaching residue; 2) leaching the leached residue with citric acid to obtain citric acid leaching solution and citric acid leached residue; The concentrations of iron ions in the leachate, the citric acid leachate and the citric acid leach residue are measured respectively, and the content of divalent iron, the content of trivalent iron and the content of elemental iron in the sponge copper are obtained respectively.
2. The measuring method according to claim 1, characterized in that The mass concentration of citric acid in step 2) is 10%-20%.
3. The measuring method according to claim 2, characterized in that In the step 2), the pH of the citric acid is 3.5-4.
0.
4. The measuring method according to claim 3, characterized in that In the step 2), the ratio of leached residue to citric acid (g:ml) is (0.6-1.2):
50.
5. The measuring method according to claim 1, characterized in that In the step 2), the leaching time is 40-60 minutes and the leaching temperature is 50-100°C.
6. The measuring method according to claim 1, characterized in that In the step 1), the ratio of sponge copper to water (g:ml) is (0.5-1):50; and the leaching time is 20-30 minutes.
7. The measuring method according to claim 1, characterized in that In the step 1), the leaching time is 20-30 minutes and the leaching temperature is 50-100°C.
8. The measuring method according to claim 1, characterized in that When measuring the citric acid leaching residue, hydrochloric acid is used for dissolution, the mass concentration of the hydrochloric acid is 36%-38% and the dissolution temperature is 100-200°C.
9. The measuring method according to claim 8, characterized in that The dosage ratio (g:ml) of the citric acid leaching residue to the hydrochloric acid is (0.3-0.6):30.